Generation of Human Blood Vessel and Vascularized Cerebral Organoids - Sun, Xin; Ju, Xiang; Zhao, Hong; You, Zhi; Han, Run; Luo, Zhen (BIO-PROTOCOL, 2023)
Brain organoids have been widely used to study diseases and the development of the nervous system. Many reports have investigated the application of brain organoids, but most of these models lack vascular structures, which play essential roles in brain development and neurological diseases. The brain and blood vessels originate from two different germ layers, making it difficult to induce vascularized brain organoids in vitro. We developed this protocol to generate brain-specific blood vessel and cerebral organoids and then fused them at a specific developmental time point. The fused cerebral organoids exhibited robust vascular network-like structures, which allows simulating the in vivo developmental processes of the brain for further applications in various neurological diseases. Key Features • Culturing vascularized brain organoids using human embryonic stem cells (hESCs). • The new approach generates not only neural cells and vessel-like networks but also brain-resident microglia immune cells in a single organoid.